2002
DOI: 10.1034/j.1399-3054.2002.1150310.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a potent allelopathic substance in rice root exudates

Abstract: A search for growth inhibitors in rice root exudates was undertaken in order to clarify the allelopathic system in rice (Oryza sativa L.). Rice seedlings inhibited the growth of cress (Lepidium sativum L.) and lettuce (Lactuca sativa L.) seedlings when the cress and lettuce were grown with rice seedlings. The putative compound causing the inhibitory effect of rice seedlings was isolated from their culture solution, and the chemical structure of the inhibitor was determined by spectral data as momilactone B. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 21 publications
4
113
0
3
Order By: Relevance
“…19) It has been found that momilactone B is excluded from rice roots and exhibits allelopathic activity against the growth of dicot plant seedlings. 5) We found that phytocassanes A to E and momilactones A and B are released from roots. 37) In contrast to momilactone B, phytocassanes do not show inhibitory activity against dicot seedling growth.…”
Section: Labdane-related Diterpene Cyclase Gene Family In Ricementioning
confidence: 78%
See 1 more Smart Citation
“…19) It has been found that momilactone B is excluded from rice roots and exhibits allelopathic activity against the growth of dicot plant seedlings. 5) We found that phytocassanes A to E and momilactones A and B are released from roots. 37) In contrast to momilactone B, phytocassanes do not show inhibitory activity against dicot seedling growth.…”
Section: Labdane-related Diterpene Cyclase Gene Family In Ricementioning
confidence: 78%
“…For example, gibberellins (GAs, phytohormone), 2) momilactones (phytoalexin; allelopathic substance, Fig. 1), [3][4][5] oryzalexins (phytoalexin, Fig. 1), [6][7][8][9] and phytocassanes (phytoalexin, Fig.…”
mentioning
confidence: 99%
“…[5][6][7] Rice plants were also found to secrete momilactone A and B from their roots into the rhizosphere and exhibit alleloapthic activities against weed plants. 1,[8][9][10] The plant rhizosphere is a densely populated area in which plant roots must compete with invading root systems of neighboring plants for space, water and mineral nutrients, and with other soil-bore organisms including bacteria and fungi. [11][12][13][14] Therefore, momilactone A and B probably play an important role in rice defense mechanism in the rhizosphere as antimicrobial and allelopathic agents.…”
mentioning
confidence: 99%
“…In addition, momilactones A and B also act as allelochemicals, as these were originally identified as dormancy factors from rice seed husks (Kato et al, 1973). More recently, momilactone B has been shown to be constitutively secreted from the roots of rice seedlings (Kato-Noguchi and Ino, 2003) as an allelopathic agent (Kato-Noguchi et al, 2002). Further, secretion of antimicrobial agents to the rhizosphere may also provide a competitive advantage for root establishment through local suppression of soil microorganisms (Bais et al, 2004).…”
mentioning
confidence: 99%